ANTIHEPATOTOXIC ACTIVITY OF TWO NEW QUERCETIN DERIVATIVES IN CARBON TETRACHLORIDE INDUCED HEPATOXICITY IN RATS - Khan, Shah Alam; Ahmed, Bahar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Quercetin, a bioflavonol is widely found in nature and possesses diverse pharmacological properties. A heterocyclic 1,4 dioxane nucleus was incorporated in Quercetin structure to obtain two structural analogues of silybin. The aim of the study was to antihepatotoxic potential of Quercetin derivatives containing 1,4 dioxane heterocyclic ring in Carbon tetrachloride (CCl4) induced hepatotoxicity in female Wistar Albino rats. Two Quercetin derivatives (QD) were synthesized by reported method. QD were administered orally at dose of 10 mg/kg, once daily for 7 days to Wistar Albino rats. A single dose of CCl4(1mL/kg) was used for inducing liver damage. Antihepatotoxic activity was evaluated by measuring levels of total proteins (TP), total albumin (TA), alkaline phosphatase (ALKP) and liver enzymes such as serum glutamate oxaloacetate (SGOT) and serum glutamate pyruvate transaminase (SGPT).QD exhibited potent antihepatotoxic activity with respect to standard drug silybon-70. However, it was observed that the Quercetin derivative having âCH2OH group in the dioxane ring exhibited better activity in comparision to unsubstituted 1,4 dixoane ring derivative.The exact mechanism by which QD protects the liver is unknown however the observed effects could be attributed to presence of 1,4 dioxane ring and due to the significant antioxidant activity of Quercetin flavone. Key words: Antihepatotoxic activity, Quercetin; Silymarin, 1,4 dioxanering, CClÂ